2007
DOI: 10.3171/jns-07/07/0109
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus organization and healing in an experimental aneurysm model. Part II. The effect of various types of bioactive bioabsorbable polymeric coils

Abstract: Degradation speed was not the only factor determining the strength of the biological response. Polysorb induced an early, unique granulation tissue that conferred greater mechanical strength to the intraaneurysmal coilthrombus complex. Enhancing the formation of this polymer-induced granulation tissue may provide a new direction for improving long-term anatomical outcomes in cases involving aneurysms embolized with detachable coils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Raymond, et al reported that nearly 50% of subsequent recurrences were present by 6 months after coiling in humans 9 . Various mechanisms underlying late aneurysm recanalization have been proposed, including 1) growth of aneurysm itself 10, 11 , 2) poor thrombus organization as a result of of the biologically inert platinum coil construction 12 , 3) instability of fresh, unorganized thrombus and degradation by fibrolysis, 4) continued transmission of blood pulsation affecting the association of coil-thrombus complex 13 , 5) lack of neointima formation across the neck of aneurysm 14 , and 6) formation of neovessels inside the aneurysms lumen exposing the aneurysm cavity to blood flow.…”
Section: Mechanism Of Recurrencementioning
confidence: 99%
“…Raymond, et al reported that nearly 50% of subsequent recurrences were present by 6 months after coiling in humans 9 . Various mechanisms underlying late aneurysm recanalization have been proposed, including 1) growth of aneurysm itself 10, 11 , 2) poor thrombus organization as a result of of the biologically inert platinum coil construction 12 , 3) instability of fresh, unorganized thrombus and degradation by fibrolysis, 4) continued transmission of blood pulsation affecting the association of coil-thrombus complex 13 , 5) lack of neointima formation across the neck of aneurysm 14 , and 6) formation of neovessels inside the aneurysms lumen exposing the aneurysm cavity to blood flow.…”
Section: Mechanism Of Recurrencementioning
confidence: 99%
“…Thus, the number of available stains is limited and the quality of the staining is inferior to that of paraffin embedded samples. In the present report, the tissue samples were processed using previously described paraffin embedding techniques 1 2. The coils were manually removed under guidance by a stereoscopic microscope and prepared using a variety of stains for multiple immunohistochemical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Each 1 mm paraffin section was then re-embedded in the paraffin and 10 μm sections were finally made using a microtome. Technical details were as previously described 1 2. Various staining techniques such as H&E, Masson Trichrome, α smooth muscle actin (αSMA), and factor VIII were performed.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…Second are the models mainly used to determine the technical proficiency of endovascular devices or to assess histopathological changes after endovascular treatment; however, this class is not used to determine the underlying mechanisms of CA formation. These models are surgically induced by creating a venous pouch mainly in the carotid artery of dogs or pigs [4245]. …”
Section: Overview Of Animal Models Of Camentioning
confidence: 99%